Seasonal variation of bacterial community in biological aerated filter for ammonia removal in drinking water treatment - Liu, Hongyuan; Zhu, Liying; Tian, Xiaohe; Yin, Yeshi (Water research (Oxford), 2017)
Biological aerated filter (BAF) is widely used in wastewater treatment plants (WWTPs) and shows potential application of micropolluted drinking water sources with a higher NH4+-N removal efficiency during short warm seasons. Here we adopted a pilot lava-based BAF setup as a pretreatment unit of drinking water treatment plant (DWTP) and achieved a great performance of ammonia removal over a two-year operation using natural river water. We respectively observed 92.62% of NH4+-N removal efficiency, 97.88% of NO2−-N removal efficiency in summer, and 77.52% NH4+-N removal efficiency in winter down to 5 °C. Based on DGGE analysis, AOB, NOB, as well as heterotrophic bacteria including genus Flavobacterium and Sphingomonas are responsible for the performance. Nitrosomonas and Nitrospira are found to be the dominant AOB and NOB in the BAF microbiota. The compositions of AOB including Nitrosomonas communis and Nitrosomonas oligotropha are different from the strains previously reported in BAF of WWTPs but similar to the observations in DWPTs. We observed seasonal bacterial shifts between summer and winter groups involved in AOB, NOB and heterotrophic genus Flavobacterium, which may be responsible for the seasonal performance fluctuation. The psychrophilic AOB belonging to Nitrosomonas likely contribute to the recovered NH4+-N removal efficiency when temperature is below 7 °C. Lack of nitrification functional psychrophilic or psychrotolerant NOB may be in charge of the severe nitrite accumulation below 7 °C. Our analysis suggests that the colonization of psychrophilic nitrifying bacteria in BAF needs at least two-year of natural acclimatization and is necessary for all-weather BAF in DWTPs. [Display omitted] •NH4+-N removal efficiency of 77.52% has been achieved over a temperature range of 5.1–8.2 °C.•Psychrophilic AOB is responsible for the great NH4+-N removal in winter.•Bacterial shift has been observed between summer and winter even in the same genus.•Two years acclimatization is needed for psychrophile colonization with raw water.